(untitled) (International Journal of Food and Nutritional Sciences, 2019)
to ensure the correctness of computer resources and deal with failures, it is important to synchronize accesses when running applications. System transactions adhere to the principles of atomicity, consistency, isolation, and durability (acid). By utilizing a reliable operating system, programmers can specify updates for various computing resources. Cloud computing allows for memory analysis for security, which is highly useful in detecting malicious activity without the need for installation on virtual machines.